Direct Fabrication of Hexagonally Ordered Ridged Nanoarchitectures via Dual Interference Lithography for Efficient Sensing Applications. Issue 8 (19th December 2013) - Jeon, Hwan Chul; Jeon, Tae Yoon; Shim, Tae Soup; Yang, Seung‐Man
<x xml:space="preserve">Abstract</x> Novel, large‐area uniform hexagonally‐ordered ridged nanoarchitectures (HORNs) can be fabricated using dual interference lithography derived from a novel prism and substrate beneath a spin‐coated photoresist (PR) film. The metallic HORN arrays provide tunable SERS effects with large‐scale sample homogeneity that depends on the number of stacks present along the z‐direction, which is determined by the PR film thickness. Furthermore, the HORN structures show significant potential for use in particle‐based or fluorescence‐based sensing platforms by forming a free suspension of ridged nanoparticles or achieving highly intensified fluorescence signals, respectively. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>